Effect of nanoemulsion loaded with macela (Achyrocline satureioides) on the ultrastructure of Staphylococcus aureus and the modulating activity of antibiotics - Ribeiro, Rayanne; Rentes, Bruna Rodrigues; Honorato, Luciana Aparecida; Kuhnen, Shirley (Frontiers in Nanotechnology, 2024)
Nanoformulations with herbal actives for treating bovine mastitis present an alternative for controlling bacterial infections in the emerging scenario of antimicrobial resistance. In this study, we investigated macela (Achyrocline satureioides) nanoemulsion (NE-ML), a formulation developed for the treatment of bovine mastitis (registered under Brazilian patent application BR 10 2021 008630 0), in the context of its bactericidal mechanism(s) of action and potential synergism with commercial antimicrobials. The effect of NE-ML on the integrity and cell permeability of Staphylococcus aureus was evaluated by measuring the electrical conductivity of bacterial suspensions exposed to different concentrations of NE-ML and by assessing the release of cellular constituents. Damage to bacterial ultrastructures was analyzed by transmission electron micrographs. The synergism of NE-ML with beta-lactam antibiotics and aminoglycosides was evaluated by the checkerboard test method against S. aureus (n=6). The relative electrical conductivity of the bacterial solution gradually increased over time, reaching high values after exposure to 1xMIC (52.3%) and 2xMIC (75.34%) of NE-ML. Total proteins were detected in the bacterial suspensions exposed to NE-ML, increasing in concentration over exposure time (p<0.05). Through bacterial micrographs, we observed that exposure to NE-ML (1xMIC) affected the integrity of the plasma membrane with invaginations in the cytosolic region and alterations in the cell wall. The increase in NE-ML concentration resulted in greater damage to the ultrastructure of S. aureus with changes in bacterial cell division patterns. When NE-ML was combined with the beta-lactam antimicrobials, the interaction was indifferent, indicating no modulation of antimicrobial resistance. In contrast, when combined with the aminoglycoside, a synergistic interaction did occur. These general findings suggest that the bactericidal action of NE-ML begins in the plasma membrane, causing alterations in its permeability and integrity, and extends to the cell wall, cytoplasm, and cell division. Although synergy was restricted to the aminoglycoside by destabilizing the bacterial cell membrane, this suggests that NE-ML can induce the entry of other actives, potentially reducing their therapeutic doses. Understanding the mechanism of action of this new nanoformulation is certain to drive pharmacological advances, broaden the perspective of its in vivo use, and improve the treatment of bovine mastitis.